2010
DOI: 10.1152/ajpregu.00846.2009
|View full text |Cite
|
Sign up to set email alerts
|

Intradermal administration of ATP does not mitigate tyramine-stimulated vasoconstriction in human skin

Abstract: Cutaneous vasodilation associated with whole-body heat stress occurs via withdrawal of adrenergic vasoconstriction and engagement of cholinergic "active" vasodilation, the latter of which attenuates cutaneous vasoconstrictor responsiveness. However, the precise neurotransmitter(s) responsible for this sympatholytic-like effect remain unknown. In skeletal muscle, ATP inhibits adrenergically mediated vasoconstriction. ATP also may be responsible for attenuating cutaneous vasoconstriction since it is co-released … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…Intradermal administration of ATP does not attenuate tyramine-stimulated vasoconstriction in human skin, in contrast to skeletal muscle vessels (Wingo et al, 2010). Changes in purine receptor expression (increase in P2Y 1 , P2Y 2 , and P2X 5 , decrease in P2X 7 ) on human lower leg epidermal keratinocytes were shown in chronic venous insufficiency (Metcalfe et al, 2006).…”
Section: G Skin Vesselsmentioning
confidence: 92%
“…Intradermal administration of ATP does not attenuate tyramine-stimulated vasoconstriction in human skin, in contrast to skeletal muscle vessels (Wingo et al, 2010). Changes in purine receptor expression (increase in P2Y 1 , P2Y 2 , and P2X 5 , decrease in P2X 7 ) on human lower leg epidermal keratinocytes were shown in chronic venous insufficiency (Metcalfe et al, 2006).…”
Section: G Skin Vesselsmentioning
confidence: 92%
“…Although several P 2 receptor subtypes have been identified, this receptor class is divided into P 2X ligand-gated ion channels and P 2Y G-protein-coupled receptor families (Burnstock & Kennedy, 1985;Burnstock, 2012Burnstock, , 2012. Intravascular sources of ATP, such as that released from endothelial cells or offloaded from red blood cells, elicit vasodilatation by acting on P 2 receptors located on the endothelium to increase vasoactive factors, such as nitric oxide (Duff et al 1954;Rongen et al 1994;Wingo et al 2010;Fujii et al 2015b). However, ATP co-released from perivascular axon terminals binds to P 2X receptors to increase the intracellular calcium concentration and contract vascular smooth muscle (Burnstock, 1988(Burnstock, , 2008.…”
Section: J a Lang And Othersmentioning
confidence: 99%
“…Furthermore, skin sympathetic nerve activity is reduced for a given cooling stimulus (Grassi et al 2003;Greaney et al 2015b). Exogenous intradermal infusion of ATP resulted in a dose-dependent VD that was mediated in part by nitric oxide (Wingo et al 2010;Fujii et al 2015b). Recent work in human skin has revealed that ATP also has a vasodilatory influence.…”
Section: J a Lang And Othersmentioning
confidence: 99%
“…However, no study to date has evaluated whether T2D modulates the cutaneous vascular response to purinergic receptor activation elicited by ATP. In human skin, low concentrations of ATP may cause vasoconstriction (Lang, Krajek, & Smaller, ), whereas high concentrations have been shown to induce a dose‐dependent vasodilatation (Fujii et al., , ; Kalsi et al., ; Wingo et al., ) without affecting sweat rate (Fujii et al., , ). Furthermore, previous work has demonstrated that ATP‐induced vasodilatation in forearm conduit arteries is impaired in individuals with T2D (Thaning et al., ).…”
Section: Introductionmentioning
confidence: 99%